Development of an Organic Agriculture Ontology for Young Agripreneurs - Chiangnangam, Sumana; Chansanam, Wirapong; Kabmala, Malee (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This study develops an ontology of organic agriculture designed to support young agripreneurs in aligning their practices with standardized organic farming systems. The purpose was to structure and represent domain-specific knowledge systematically, enabling its application in decision support and information systems. The ontology construction followed a three-stage framework: defining the purpose, developing the ontology, and conducting evaluations. A knowledge engineering approach with seven steps was applied, and the Hozo Ontology Editor served as the development tool. The resulting ontology comprises 127 classes, including nine core categories—Young Agripreneurs, Organic Farming, Products, Business, Markets, Agriculture Processes, Agencies, Services, and Document—supported by 118 subclasses. Furthermore, 31 properties and interrelationships were defined to represent the conceptual linkages within the domain. Evaluation by domain experts, based on five criteria—definition and scope, class identification, property specification, instance creation, and applicability—confirmed a high level of appropriateness. The final ontology, delivered in OWL format, provides a robust knowledge model for organic agriculture. Its significance lies in facilitating knowledge-based recommender systems that enhance decision-making and planning for young agripreneurs, ultimately contributing to sustainable agricultural entrepreneurship.